(untitled) (Bangladesh Journal of Plant Taxonomy, 2016)
Foliar epidermal characters of nine Cordia L. species found in Egypt are investigated. Glandular trichomes are observed in C. boissieri A. DC. and C. cylindristachya (Ruiz & Pav.) Roem. & Schult., while eglandular trichomes are predominant in all studied species. Different stomatal characters were examined including: shape, size, rims, stomatal level, aperture, cuticular deposition and wax ornamentation. The retrieved results showed a great variation among the studied species. The observed trichomes and stomata were used to construct two different taxonomic keys. Bangladesh J. Plant Taxon. 23(2): 119-131, 2016 (December)